MENINGKATKAN KETERAMPILAN BACA TULIS QUR’AN AWAL MELALUI KEGIATAN MENCOCOK PADA KELOMPOK B DI RA AL-QUR’AN SUNAN KALIJOGO GENITRI KARANGPLOSO MALANG - Chomsah Yuni Syarah; Eko Setiawan; Ari Kusuma Sulyandari (UNISMA, 2022)
This research is entitled Improving Early Qur'an Literacy Skills through Matching Activities in Group B in Ra Al-Qur'an Sunan Kalijogo Genitri Karangploso Malang. The background of this research is about improving the literacy skills of the early Qur'an through matching methods. This research method uses classroom action research methods (Classroom Action Research). Data collection techniques are carried out using observation methods, documentation, and interviews. From the results of preliminary research in RA Al-Quran Sunan Kalijogo Karangploso Malang shows that the increase in the first cycle of the beginning of 33% increased to 89% in cycle II. With the matching method, it can improve the literacy skills of the early Qur'an in group B RA Al-Quran Sunan Kalijogo Karangploso Malang